2002
DOI: 10.1055/s-2002-28469
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Preservation by Prolonged Sensory Protection

Abstract: The functional recovery of a muscle target following nerve repair is inversely related to the denervation time: i.e., the longer the muscle denervation, the poorer the functional outcome following nerve reconstruction. The trophic and protective effects of sensory innervation to a motor nerve, following prolonged denervation (greater than 6 months), have been studied. Following proximal transection of the musculocutaneous nerve (MC) close to its C6 origin in 10 adult male Sprague-Dawley rats, the severed nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…4,12 Patients have reported a perception of muscle tension (stretch) with muscle activity during sensory protection and improved function (walking) resulting from improvement in ankle position even before significant changes in motor recovery of the targets. 24 The molecular and cellular mechanisms responsible for the functional extrafusal fiber recovery are under investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,12 Patients have reported a perception of muscle tension (stretch) with muscle activity during sensory protection and improved function (walking) resulting from improvement in ankle position even before significant changes in motor recovery of the targets. 24 The molecular and cellular mechanisms responsible for the functional extrafusal fiber recovery are under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,5,11,12 This strategy, called "sensory protection," uses a readily available sensory nerve to temporarily innervate a denervated muscle until the injured motor nerves regenerate and become available for surgical reconstruction. We have shown that temporary sensory innervation improves functional recovery of denervated skeletal muscle following reinnervation.…”
mentioning
confidence: 99%
“…Sensory nerve cross-anastomosis to the distal motor nerve (sensory protection) significantly improves muscle weight, with larger compound muscle action potentials, less fiber atrophy and connective tissue hyperplasia than in denervated muscle (Hynes et al, 1997;Bain et al, 2001). An increased number of motor endplates is also found in muscles that receive sensory protection (Papakonstantinou et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…When the motor nerve was connected end-to-end to the sensory nerve ("Sensory protection"), it seemed to provide trophic environment to minimize muscle atrophy until a motor donor nerve became available. Although incapable of forming excitable neuromuscular junctions, sensory nerves were found to exert powerful trophic effects on denervated muscle fibers [12][13][14] .…”
Section: Discussionmentioning
confidence: 99%